Pre-service Teachers Learning to Teach English as a Foreign Language to Preschool Learners in Macau: A Longitudinal Study - Reynolds, Barry Lee; Liu, Sylvia; Ha, Xuan Van; Zhang, Xiaofang; Ding, Chen (Frontiers in Psychology, 2021)
Language teacher beliefs have received increasing research attention for the past few decades. However, little is known about the beliefs of pre-service teachers in the pre-primary English as a foreign language (EFL) education context. This qualitative case study extends this line of inquiry by investigating the trajectory of student teachers' beliefs about teaching English to pre-primary learners in Macau within a teacher education course. The participants included 60 pre-service teachers taking an English Language Activities course in their third year of a 4-year Bachelor of pre-primary education program. The data comprised written reflections collected at three points in time during the 16-week course: at the beginning of the course, mid-way through the course, and at the end of the course. The findings showed five broad themes, constituted from 15 subthemes, regarding (1) learners and learning, (2) teaching, (3) subject, (4) self, and (5) learning to teach. The major themes have been documented in the literature, but several subthemes were identified for the first time in the context of pre-primary EFL teacher education. More importantly, the findings revealed that some of the subthemes were newly shaped and several subthemes were reshaped as a consequence of taking the course. The findings were interpreted in relation to the content of the course, the experiential learning opportunities, the pre-service teachers' prior experiences of language learning and teaching, and the local language teaching and learning context. Implications for pre-service teacher education programs are discussed.